2019
DOI: 10.3390/ijerph16152772
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Smokers’ Experiences and Opinions of Techniques Aimed to Address Barriers and Facilitators to Smoking Cessation: A Qualitative Study

Abstract: Pregnant women experience certain barriers and facilitators (B&Fs) when trying to quit smoking. This study aimed to elicit women’s views on techniques that could help overcome or enhance these. Semi-structured interviews were conducted with 12 pregnant women who had experience of smoking during pregnancy. Participants were prompted to discuss experiences of B&Fs and give suggestions of techniques that could address these appropriately. A thematic analysis was conducted using the one sheet of paper meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
0
15
0
2
Order By: Relevance
“…There is, however, only limited research on the uptake of services by pregnant women (Naughton et al., 2020), with much of the current literature focussed on the barriers to, and facilitators of, pregnancy smoking cessation (e.g. Campbell et al., 2018; Fergie, Campbell, et al., 2019; Fergie, Coleman, Ussher, Cooper, & Campbell, 2019; Flemming et al., 2016; Naughton et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, only limited research on the uptake of services by pregnant women (Naughton et al., 2020), with much of the current literature focussed on the barriers to, and facilitators of, pregnancy smoking cessation (e.g. Campbell et al., 2018; Fergie, Campbell, et al., 2019; Fergie, Coleman, Ussher, Cooper, & Campbell, 2019; Flemming et al., 2016; Naughton et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Outro fator determinante quanto à estratificação do risco gestacional é a multiparidade, uma vez que os resultados mostraram maior número de filhos em mulheres pertencentes aos grupos intermediário e alto risco, corroborando com a pesquisa realizada em Aracajú, SE, que identificou que um terço das gestantes pertencentes ao grupo de alto risco tem três ou mais filhos 16 . tornando-se um importante problema de saúde pública 11,15,17,18 .…”
Section: Discussionunclassified
“…Statistics show that approximately 50% of women who smoke quit during their pregnancy [ 5 ]. Previous research has concluded that it is important to identify why certain women fail to engage with smoking cessation services whilst pregnant [ 37 ]. This study found that some women may not be ready to quit smoking as other factors may be hindering them such as issues surrounding mental well-being [ 23 , 38 ].…”
Section: Discussionmentioning
confidence: 99%